2015
DOI: 10.3892/ol.2015.3786
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of tumor necrosis factor-α enhances apoptosis induced by nuclear factor-κB inhibition in leukemia cells

Abstract: Abstract. Inhibition of nuclear factor-κB (NF-κB) results in antitumor activity in leukemia cells, and may be a potential therapeutic strategy for the treatment of leukemia. However, a significant limitation of NF-κB inhibition in the treatment of leukemia is the low efficiency of this technique. NF-κB inhibitor treatment induces apoptosis in leukemia cells; however, it additionally causes inflammatory molecules to induce increased sensitivity of healthy hematopoietic cells to cell death signals, therefore lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…TNF-α upregulates expression of matrix degrading matrix metalloproteinases (MMPs 2 ) and two major aggrecanases (ADAMTS-4 and ADAMTS-5) by NPCs [1618]. PI3K and its target PKB/Akt have emerged as critical signaling molecules that regulate multiple cellular processes, including survival and proliferation in numerous systems [1921]. Matthew et al [22] demonstrated that PI3K and Akt could suppress TNF-induced apoptosis in MCF-7cells, while simultaneously increasing NF-κB activity.…”
Section: Introductionmentioning
confidence: 99%
“…TNF-α upregulates expression of matrix degrading matrix metalloproteinases (MMPs 2 ) and two major aggrecanases (ADAMTS-4 and ADAMTS-5) by NPCs [1618]. PI3K and its target PKB/Akt have emerged as critical signaling molecules that regulate multiple cellular processes, including survival and proliferation in numerous systems [1921]. Matthew et al [22] demonstrated that PI3K and Akt could suppress TNF-induced apoptosis in MCF-7cells, while simultaneously increasing NF-κB activity.…”
Section: Introductionmentioning
confidence: 99%
“…Nuestros datos revelan que ni las caseínas ni el caseinato de sodio alteran la viabilidad celular detectada mediante el MTT, una prueba que evidencia la actividad metabólica mitocondrial (que solo tiene lugar en células vivas) (24), lo cual no coincide con la ligera inducción de translocación de fosfatidilserina causada por todas las caseínas, especialmente, por el caseinato de sodio (23 %) y la caseína α (16 %), justamente en las condiciones en que se observa la liberación de TNF-α, un promotor de la inducción de la apoptosis (25). La translocación de fosfatidilserina a la cara externa de la membrana es un evento temprano de inducción de la apoptosis y, por lo tanto, es reversible (26).…”
Section: Discussionunclassified
“…Furthermore, Karakaş et al (2012) showed that Melilotus officinalis and Melilotus alba extracts have great tumor inhibition activities. From a mechanistic point of view, however the anti-inflammatory effect of Melilotus extract could be attributed to the inhibition of TNF-a mRNA, COX-2 mRNA, and NF-kB (Zhang et al 2007), such candidates are implicated in the apoptotic pathways in cancer cells (Dong et al 2015), the underlying anticancer mechanisms of Melilotus extracts have remained completely unknown. Therefore, we aimed through studying the effect of M. indicus extract on cell proliferation of human hepatocellular carcinoma cell lines to elucidate its anticancer mechanism.…”
Section: Introductionmentioning
confidence: 99%